CYBERSECURITY IN VALIDATION: PROTECTING SYSTEMS IN A DIGITALLY-CONNECTED WORLD - Devkumar Darshan Rajpuriya (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the critical intersection of cybersecurity and system validation in the pharmaceutical industry, focusing on the evolving challenges and solutions in protecting digitally connected pharmaceutical systems. It examines the transformation of validation processes to incorporate cybersecurity measures, addressing regulatory compliance requirements, risk assessment protocols, and security control implementations. The discussion encompasses the integration of security considerations throughout the validation lifecycle, continuous monitoring strategies, and emerging technologies. Special attention is given to the implementation of advanced security frameworks, predictive maintenance approaches, and future considerations in maintaining secure pharmaceutical operations. The article provides insights into best practices for securing pharmaceutical systems while ensuring compliance with regulatory requirements and maintaining operational efficiency